HOW SECOND LANGUAGE ACQUIRED AT SCHOOL: SOME FACTORS INFLUENCING L2 ACQUISITION: SOME FACTORS INFLUENCING L2 ACQUISITION - Fajar Susanto (Buana Pendidikan, 2015)
The aim of this article is to discuss how children acquire the second language at school from psycholinguistic perspective. Second Language (L2) is a language that is acquired after a child has acquired the first language (L1). A child will grow up with a social environment and with a language he uses. If a child lives in a bilingual or multilingual society he may speak more than one language. But how can a child acquire a second language after the first language? As we know that language acquisition is not an easy process. It may be said it is a complicated process although humans sometimes are not conscious with this condition. Language acquisition according to Ellis can occur naturally or formally. L2 acquisition is also influenced by some factors such as motivation, age, formal presentation, first language, and environment. Besides that, teacherÃ‚â€™s language also has some important roles for the learners in learning a second language